2009
DOI: 10.1080/13576500802387692
|View full text |Cite
|
Sign up to set email alerts
|

Human handedness and scalp hair whorl direction: No evidence for a common cause

Abstract: A much wider variation in many physical and cognitive behaviours exists among left-handers than among right-handers, which is evidence for more than one aetiology of left-handedness. Despite these findings some researchers are still attempting to link left-handedness to a single cause, most recently genetic determination, by pairing left-handedness with a presumed genetically based characteristic. One of these characteristics is scalp hair whorl, which may be clockwise, counter-clockwise (purportedly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The number is too small to justify a separate category. Although alternative cutoff points have been empirically validated and recommend for handedness classification [4], there remains no consensus regarding the best classification method among researchers who use the EHI [52]. Furthermore, one of the purposes of this study is to compare prevalence of handedness based on preference and performance measures, and a consistent classification criterion, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The number is too small to justify a separate category. Although alternative cutoff points have been empirically validated and recommend for handedness classification [4], there remains no consensus regarding the best classification method among researchers who use the EHI [52]. Furthermore, one of the purposes of this study is to compare prevalence of handedness based on preference and performance measures, and a consistent classification criterion, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The number is too small to justify a separate category. Although alternative cutoff points have been empirically validated and recommend for handedness classification [4], there remains no consensus regarding the best classification method among researchers who use the EHI [52].…”
Section: Discussionmentioning
confidence: 99%
“…Klar et al [9][10][11][12] published a number of research papers on the presence or the absence of relevance between dominant handedness and PW. One of their studies reported that PW was associated with hemispheric language dominance and homosexuality [13,14]. Further, numerous studies investigated PW.…”
Section: Discussionmentioning
confidence: 99%